Cultural Pragmatics in Edward Albee’s The Zoo Story - Dodhy, Shamaila (k@ta: A Biannual Publication on the Study of Language and Literature, 2016)
Cultural Pragmatics is essential for a close examination of Edward Albee’s The Zoo Story. It depicts how changing cultural values impinge on the behavioral patterns of the individual. This article attempts to investigate how intentions of interactants are culture driven and culture related. Collapse of cultural values and discontinuity of conventional view points and beliefs led people to a state of disorientation. The speaker’s discourse highlights the character’s inability to communicate to suggest the emptiness of hackneyed social intercourse resulting in psychopathological diseases among individuals.